안락사 문제의 법철학적 고찰 - 임미원; Mi Won Lim (윤리연구, 1(71), 2008)
안락사-존엄사를 둘러싸고 다시 제기된 최근의 논쟁은, 근본적으로 죽음의 문제가 역사성과 사회성을 갖는 테마이며 특히 근대적 自然死의 이념에 대한 비판적 이해가 전제되어야 함을 보여준다. 이 자연사 개념을 매개로 하여 다양하게 제기되는 생명윤리적-정책적 제안들 중 네오막시즘이 주장하는 ‘自然死에의 평등한 권리’와 포스트모더니즘이 비판하는 ‘自然死의 이데올로기’는, 自然死-安樂死의 문제가 갖는 사회적-규범적 의미를 적절히 보여준다고 할 수 있다. 이제 안락사-존엄사의 문제는 환자에 대한 의사의 후견적 보호관계를 전제로 한 형법적 규율의 대상을 넘어 환자 자신의 인간존엄 내지 기본적 인권이라는 차원에서 제기되는 헌법소원의 대상, 즉 적극적 권리요구의 대상으로 변해가고 있으며, 환자의 자기결정성의 권리 대 환자의 복지에 대한 의사의 배려의무 내지 국가의 생명 보호의무라는 외적 갈등구조뿐 아니라, 오히려 환자의 자기결정성 대 이로부터 귀결되는 환자자신의 자기처분성이라는 내재적-자기모순적 관계가 본질적인 것이 되고 있다. 그런 점에서, 자율인가 타율인가의 차원보다는 자율적인가 자기처분적인가의 차원에서 자율성과 자연성의 합치가능성, 즉 스스로의 한계 내지 경계 지점으로서 ‘자연성’을 인정하는 ‘자율성’이 생명의료 윤리적으로 어떻게 실현가능한가의 문제로 집중된다고 할 수 있다. 이런 안락사 문제의 규범적 난제로는 첫째, 정당화 근거의 문제, 둘째, 자기결정권의 한계범위의 문제, 세째, 행위 간의 구별경계의 문제 등이 있다. 이와 관련해 최근 두드러지는 안락사에 대한 사법적 규율화의 시도들 - 특히 환자의 주관적 의사의 확인 방식으로서 ‘사전유언’으로 집중되는 - 은, 근본적으로 어떻게 자연성에 반하지 않는 자율적 방식의 안락사가 가능한가에 대한 총체적인 사법적 대답이라고 할 수 있다. The normative judgment about the euthanasia-problem largely depends on the understanding of the socio-historical concept of death and especially ‘natural death’. The idea of natural death has influenced on the modern bioethical and -political perspectives and has played a great role in the euthanasia-debate. Foremost the neomarxist and postmodernist views, with their own analyses on the 'natural death'-concept, clarify the social and normative meaning of euthanasia-debate. The neomarxists assume the positive role of the 'natural death'-idea in its social and medical context and defend the equal rights to natural death. But the postmodernists radically criticize the 'ideology of natural death' and contradict the biopolitical concept of the postmodern governance in general. The both analyses make clear that the euthanasia has its justification only in the exercise of the autonomy of patients which results by no means in the unnatural self-disposition. Nowadays there are growing recognition of this point and it is strived to introduce the moderate regulation on the euthanasia-practice. Foremost the 'advance directives (Patientenverfügung)' are proposed as an alternative to the subjective actual will of patients. This method might bring the negative social effects, nevertheless it can support the patient's primary interest in the autonomous self-decision. KCI Citation Count: 5